Exercise induced muscle weakness in a young adult: McArdle’s disease unusual presentation - Kalsoom, Hira; Haseeb Mukhtar; Rizwana Kitchlew Latif (Journal of the Pakistan Medical Association, 2023)
McArdle’s disease (Glycogen storage disease type V) is a rare inherited autosomal recessive disease involving defect in enzyme, glycogen phosphorylase (PYGM) which results in accumulation of glycogen mainly affecting skeletal muscles. It commonly presents in childhood and rarely in adults with symptoms like exercise intolerance, muscle weakness, cramps and fatigue. Herein, we report an unusual case of a 22 years old male in Pakistan with probable McArdle’s Disease presenting with repeated episodes of generalized cramping muscle pain, exercise intolerance and haematuria. The diagnostic approach to identifying this disease as well as the differentials of other rare types of skeletal muscle disorders that should be kept in mind while dealing with a similar clinical picture, irrespective of the age of presentation, have been discussed. Keywords: Glycogen Storage Disease Type V, Myoglobinuria.